Sesja satelitarna - Rak płuca - koniec czy początek możliwości diagnostyczno-terapeutycznychCardiac tamponade as the initial symptom of non-small cell lung cancer – case report (Przewodnik Lekarza/Guide for GPs Supplement, 2008)
The heart and pericardium are involved in about 10% of patients with malignant disease and 40% of those due to lung cancer. In most cases clinical symptoms associated with heart and pericardium involvement are absent and diagnosis is made in autopsy. Cardiac tamponade as the initial presentation of lung cancer is rare. The case of a 68-year-old man with recurrent life-threatening cardiac tamponade is described. The non-small cell lung cancer diagnosis was made after using a variety of specialist diagnostic procedures.